1976
DOI: 10.1002/pssb.2220750119
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron Masses in Semiconducting Bi1−xSbx Alloys

Abstract: Cyclotron resonance measurements are carried out on a great number of semiconductive BiI-.Sb, alloys in the range of 0.07 < z 2 0.17. The measuring frequencies are 35 and 70 GHz, and the measurements are carried out at helium temperatures. For the smallest cyclotron mass, a linear relationship to the antimony concentration is found. The more rapid increase of the great cyclotron masses and the associated increase of the elongation of the iso-energy surfaces with increasing antimony concentration presents the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Corresponding to the values of the small band-edge cyclotron mass r n $ O (~) [6] and the literature data for the energy gap 141, simultaneous the relation is satisfied (see equation ( As compared with this, the increase in the anisotropy of the cyclotron masses with rising energy gap, which is found in the range 0.10 x s 0.15, represents a peculiarity. This peculiarity and likewise the behaviour of y in the vicinity of the critical pressure p,.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Corresponding to the values of the small band-edge cyclotron mass r n $ O (~) [6] and the literature data for the energy gap 141, simultaneous the relation is satisfied (see equation ( As compared with this, the increase in the anisotropy of the cyclotron masses with rising energy gap, which is found in the range 0.10 x s 0.15, represents a peculiarity. This peculiarity and likewise the behaviour of y in the vicinity of the critical pressure p,.…”
Section: Discussionsupporting
confidence: 53%
“…(The calculations in [lo] were carried out for the quasi-classical magnetic field range and an ellipsoidal model for the dispersion relation of the electrons.) I n this case, t o obtain (6) it is necessary that the contributions to the wave vector k which are connected with the dielectric constant of the lat- This redistribution is a consequence (i) of the increase in the state density of the energy levels and (ii) of the simultaneous shifting of the levels in the magnetic field (cf., for example, ["I). Corresponding to the cyclotron masses and spin splitting parameters for B parallel to the axes 2' and 3', the first leads first of all to a decrease of A with rising magnetic field after the quasi-ellipsoid a has reached the ultraquantum state (only one occupied level).…”
Section: Methodsmentioning
confidence: 99%
“…At the L-point of the Brilluoin zone, there is another valence band, separated from the conduction band by a small gap e g E13.6 meV at 0 K [6,7]. The results of studies on the Bi-Sb solid solutions energy spectrum (see, e.g., [6][7][8][9][10][11][12][13]) showed that with increasing Sb content, the T-band moves down in energy, and the direct gap e g , separating the bottom of the conduction band and the top of the valence band in the L-point of the Brilluoin zone (terms L a and L s , respectively), rapidly decreases and at a certain concentration x 1 (x 1 ffi2. 3 various authors) becomes zero and a gapless state is realized.…”
Section: Introductionmentioning
confidence: 99%
“…1). To the best of our knowledge, superconducting BiSb-based junctions have not yet been used; we fabricated such junctions not long ago [9], although the unique electron properties of this material have long been known [10]. One of these properties is an abnormally low effective mass of electrons m ‫ء‬ equal to 0.9 3 10 23 m 0 where m 0 is the mass of a free electron and, hence, a very great de Broglie wavelength l ഠ 800 nm in single crystals with 6 at.…”
mentioning
confidence: 99%